(untitled) (College of Basic Education Research Journal, 2025)
This research dealt with a study of treatment of some industrial and similar dyes with (o-tolidin (2,6-dimathelanlin) (2,4,6-Tri-mathelanlin) by applying adsorption technique using material Atablekite clay available in western regions of Iraq, characterized with mass availability and at low economic cost. This material was prepared by crushing, washing, drying and studying it for adsorption of the above – mentioned dyes. Aqueous solutions of these dyes were prepared using specific proportion of water with solvent (ethanol) and determining optimum conditions for the best amount of adsorbent, which was (0.1g),as well as the best concentration, temperature and pH, using single – meal method. ln this research, thermodynamic values were calculated. (∆S,∆H,∆G) at equilibrium. It became clear through this research that enthalpy value was equal to a negative value (,∆H=-) meaning that reaction is exothermic, and value of (∆G=-) indicates spontaneity of reaction. It also became clear for researchers that adsorption process of these dyes has a physical characteristic, physical adsorption, meaning association of adsorbent and adsorbed material through van der Waals bonds. This research also included calculating some dye adsorption isomers such as Langmuir-Freundlich and obtaining some important values such as(b) (QMAX) and (n) which provide confirmation of values obtained in thermodynamic study.